A qualitative exploration of facilitators and barriers of adherence to time-restricted eating. (1st November 2022) - O'Connor, Sydney G.; Boyd, Patrick; Bailey, Caitlin P.; Nebeling, Linda; Reedy, Jill; Czajkowski, Susan M.; Shams-White, Marissa M.
Abstract: Time-restricted eating (TRE), a dietary strategy that involves limiting daily energy intake to a window of ≤12 h is appealing for weight management and metabolic health due to its relative simplicity and the ability to consume ad libitum diet during eating windows. Despite the potential utility of TRE for improving health and reducing disease, the feasibility of adherence depends upon a variety of multilevel factors which are largely unexplored. The primary aim of our study was to explore facilitators and barriers of adherence to TRE among community-dwelling individuals. Semi-structured qualitative interviews were conducted among 24 individuals (50% male; M age: 34, range: 18–57; 58% overweight/obese) who currently or formerly practiced TRE. Thematic analysis identified facilitators of and barriers to TRE adherence at multiple levels of influence (i.e., biological, behavioral, psychosocial, environmental). Key facilitators of adherence included improvements in physical health and energy levels, alignment with other aspects of diet, exercise and sleep patterns, self-monitoring and positive psychological impacts, social support, and busy or regular schedules. Key barriers included negative physical health effects, feelings of hunger and sluggishness, difficulty in skipping valued baseline eating routines or inadequate diet quality during the eating window, misalignment of TRE with 24-h activity behaviors, difficulties with self-monitoring, the need to mitigate negative feelings, social situations that discourage TRE, and irregular or idle schedules. Results illustrate that key drivers of adherence differ across individuals and their unique settings and that multiple drivers of behavior should be considered in the successful implementation of TRE. Findings may inform interventions seeking to tailor TRE schedules to fit individuals' diverse behavioral patterns and preferences, thereby optimizing adherence.